At the Ayurveda Hospital, Practices for Controlling and Preventing Infection must be Disseminated (AYUSHDHARA, 2023)
In order to achieve health and alleviate illness, Ayurveda, an ancient science of life, takes a holistic approach. The fundamental idea of health that guides modern medicine is present in Ayurveda. A major component of its conception is the preservation of a healthy person's health [1]. Sankraman (infection) is a concept that has been well-studied, as has the control and prevention of it. Ancient science overemphasizes the need of personal hygiene, seasonal maintenance, and environmental preservation for good health, the control of sickness, and the prevention of its spread. Due to government support and growing public awareness, Ayurvedic medicine is now becoming more and more popular.